Chemoselective hydrogenation of nitrobenzyl ethers to aminobenzyl ethers catalyzed by palladium–nickel bimetallic nanoparticles. Issue 49 (9th December 2015) - Chen, Wenwen; Bao, Hailin; Wang, Dingsheng; Wang, Xinyan; Li, Yadong; Hu, Yuefei
Abstract: A highly efficient and chemoselective hydrogenation of nitrobenzyl ethers to aminobenzyl ethers was developed by using a novel palladium–nickel bimetallic nanocatalyst. Since the catalytic selectivity was resulted from the synergistic effects between two metals rather than the traditional catalyst poisons, the hydrogenation proceeded smoothly under additive-free conditions. Thus, the work-up procedure was as simple as to recover the catalyst by a magnetic separation and then to evaporate the solvent. Graphical abstract: